2022
DOI: 10.3390/scipharm91010002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Silico Screening Analysis of Artabotrys sumatranus Leaf and Twig Extracts for α-Glucosidase Inhibition Activity and Its Relationship with Antioxidant Activity

Abstract: Artabotrys sumatranus is one of the Artabotrys species, which lives in Sumatera, Java, and Borneo in Indonesia. No research has been found related to its activity. The objective of this study was to explore the potential of A. sumatranus leaf and twig extracts as the source of an anti-diabetic agent through the α-glucosidase inhibition mechanism, as well as the relationship between the antioxidant and the α-glucosidase inhibition activities in these extracts. Ethanol extracts from leaf and twig A. sumatranus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…at a concentration of 7–8 µL mL −1 ( Gakuubi et al., 2017 ). Certain reports published the effect of flavonoids as an antifungal effect ( Orhan et al., 2010 ; Jin, 2019 ), and observed a flavonoid, a polyphenol compound (7, 9-Di-tert-butyl-1-oxaspiro (4, 5) deca-6, 9-diene-2, 8-dione) ( Rosa et al., 2022 ), in TMFE. The proposed mechanism of antifungal activity by use of MFE may be due to the inhibition of spore germination by preventing the emergence of a normal germ tube, leading to abnormal swelling and the branching of hyphae ( Paul et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…at a concentration of 7–8 µL mL −1 ( Gakuubi et al., 2017 ). Certain reports published the effect of flavonoids as an antifungal effect ( Orhan et al., 2010 ; Jin, 2019 ), and observed a flavonoid, a polyphenol compound (7, 9-Di-tert-butyl-1-oxaspiro (4, 5) deca-6, 9-diene-2, 8-dione) ( Rosa et al., 2022 ), in TMFE. The proposed mechanism of antifungal activity by use of MFE may be due to the inhibition of spore germination by preventing the emergence of a normal germ tube, leading to abnormal swelling and the branching of hyphae ( Paul et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Prophylactic activity, antioxidant, antibacterial, anti-diarrhoeal, anti-inflammatory, antihyperglycemic activity (Mathi et al, 2015;Senthil et al, 2016;Mohammed et al, 2016;Sahi 2016) γ-Tocopherol 0.54 Antineoplastic (Cooney et al, 1993, anticarcinogenesis (Takahashi et al, 2009, antiinflammatory (Reiter et al, 2007, antioxidant (Brigelius-Flohe et al, Antioxidant, anti-inflammatory (Choi et al, 2013;Nair et al, 2018), insecticidal and nematicidal (Chen et al, 2015), antibacterial (Aissaoui et al, 2019), antiviral (Leila et al, 2019) Anti-tumor (Takahashi et al,1995), antiinflammatory (Das and Himaja 2014), larvicidal effects (Sowmiya et al, 2017) Antimicrobial, antioxidant, anti-cancer, hypoglycaemic activities (Prajna et al, 2016;Sunita et al, 2017), anti-inflammatory and antiallergic properties (Zhang et al, 2019), αglucosidase inhibitors (Rosa et al, 2023).…”
Section: Results Results Resultsmentioning
confidence: 99%
“…Ascorbic acid was used as the positive control solution. The analysis results were expressed as Fe 2+ mol/g extract and can be calculated using the following formula (Rosa et al, 2023):…”
Section: α-Glucosidase Inhibition Assaymentioning
confidence: 99%
“…The following formula (Rosa et al 2023) was used to calculated total TPC which was shown as milligram of gallic acid equivalent (GAE) per gram extract. GAE in ppm for sample was expressed as , and was the extract concentration in ppm.…”
Section: α-Glucosidase Inhibition Assaymentioning
confidence: 99%
See 1 more Smart Citation